Ice Core Record Variations of Atmospheric Cu, Zn, Cd, Pb, and Pb Isotopes During the Past 800 Years in Mount Everest - Hong, S.; Lee, K.; Do Hur, S.; Hou, S.; Nunes, Laurie; Boutron, C.; Barbante, C. (Maralte B.V., 2012)
Cu, Zn, Cd, and Pb concentrations and Pb isotopic composition were measured in high-altitude Mount Everest ice cores, spanning an 800-year period from 1205 to 2002 ad in order to evaluate the extent to which human activities have affected the natural atmospheric cycles of these elements in Central Asia. The results show that concentrations of Cu, Zn, Cd, and Pb in the remote Himalayan atmosphere were primarily of natural origin until the mid-20th century. Significant increases in crustal enrichment factors (EFs) in comparison with the average preanthropogenic EF value are observed for the measured metals during the recent decades, with contrasting time trends for the different metals. Such recent enhancements in EFs are attributed to massive anthropogenic emissions of Cu, Zn, and Cd mainly from combustion of fossil fuel and production of nonferrous metals, while increased emissions of Pb are attributed to combustion of fossil fuels as well as leaded gasoline usage in South Asia. Significant variations in the Pb EFs and 206Pb/207Pb isotope ratios starting from the 1970s characterize the unambiguous atmospheric Pb pollution and the time-dependent evolution of industrial Pb inputs as a result of industrial developments in South Asia.